Analisis Variabel Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Pengiriman Barang di PT. Eka Multi Logistik - M. Azhar Shauqy; Abdul Rahman; Arif Fuddin Usman; Andi Herlina; Rifkah Fitriah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
PT.Eka Multi Logistik is a land and sea transportation management (JPT) service company that has been involved in the field of goods transportation for Export, Import and Local since 2018, located on Jl. Kalimantan NO.65/67 Makassar City, South Sulawesi Consumer or customer satisfaction can be influenced by various factors that are closely related, including price and service quality. The aim of this research is to see whether there is an influence between the independent variables (price and quality of service) on the dependent variable (customer satisfaction). This research was carried out at PT. Eka Multi Logistik using multiple linear regression analysis methods. The research results show the results of the calculated f test (13.350) > f table (3.231) with a significance of 0.000 <0.05, so H0 is rejected and Ha is accepted, so it can be interpreted that the price and service quality variables have a positive and significant effect on customer satisfaction at PT. Eka Multi Logistics.